BMT microfinance management model: Developing sharia financing instruments for sharia-based MSMEs - Jawad Z. Salic; Adhelia Desi Prawestri; Baniady Gennody Pronosokodewo; Yuni Astuti (Qualitative Research of Business and Social Sciences, 2026)
This study examines the use of Baitul Maal wa Tamwil (BMT) microfinance in supporting Sharia-based Micro, Small, and Medium Enterprises (MSMEs) through an analysis of capital management behavior and Islamic financial literacy. Using purposive sampling, a total of 59 Sharia-compliant MSME operators in the Special Region of Yogyakarta were surveyed through structured questionnaires that capture indicators of Sharia capital foundations, microfinance utilization, and operational financing support. The collected data were analyzed using Exploratory Factor Analysis (EFA) to identify the latent constructs underlying MSME behavior in adopting BMT-based financing. The EFA results extracted three dominant factors—Sharia-Based Capital Foundations, Function of Sharia Microfinance Utilization, and Operational and Innovation Support Through Sharia Financing—which jointly explain 51.821% of the total variance. These findings demonstrate that BMT plays a significant role in providing halal-based capital, supporting MSME operational efficiency, and strengthening innovation capacity within a Sharia-compliant framework. The study provides empirical evidence on the importance of Sharia microfinance institutions in enhancing MSME sustainability and contributes a model that may be adapted to emerging Sharia-based MSME ecosystems in other countries, such as the Philippines.